Analisis Keterlibatan Komunitas dalam Industri Permainan Daring di Indonesia - Ahdiyat, Moh. Adli; ., Irwansyah (Master of Communication Science Program, Universitas Diponegoro, 2018)
In this digital era, the entertainment industry began to be enriched by the presence of the online gaming industry. In Indonesia, video games that were once considered as a hobby, now have turned into commodities with millions hundred dollar profits per year. The online game industry cannot be separated from the role of stakeholders, including the audience as consumers. The audiences or consumers of the online game industry are active members of the online game community that shares the same perceptions, principles, values, and interests by playing online games. In this article, the author aims to describe the role of the online game industry in creating a community, both virtual (online) community or real community (offline), and describing various business and industrial potentials that exist within the online game community. The findings in this article are: 1) The online game industry in Indonesia plays a role in forming an online and offline community that considered as an important community by the Indonesian government and society in general. 2) Through activity in the online and offline communities, gamers can take advantages of their hobbies as a way to generate financial benefits, 3) The potential of business in the online gaming community can significantly help the development of the online game industry. The results of this study suggest the development of scientific research on the online gaming industry, so it can provide a significant influence on the development of the online game industry.